Legal Uncertainty Regarding Abuse of Authority That is Harming State Finance in Indonesia (Journal of Private and Commercial Law, 2021)
This study aims to discuss issues regarding the legal certainty of criminal acts of abuse of authority and problems regarding the return of state financial losses in handling corruption cases in Indonesia. To examine these problems, a normative juridical research method was used using secondary legal data consisting of primary legal materials and secondary legal materials. Based on the results of the study, it is known that the handling of cases of Corruption Crimes cannot be separated from the influences of the bureaucracy and political factors, both from the legal provisions that govern it and from unscrupulous government officials with strategic positions in the Government who are perpetrators of abuse of authority that is detrimental to finances. country. However, there is a discrepancy in the regulation regarding abuse of authority in the Law on government administration and the Law on criminal acts of corruption in Indonesia, especially in terms of recovering state financial losses.